Development of Clutch Design Using Waste Wood bark, Nuts and Coconut Fiber - Soeprapto, Etwin Fibrianie; maulita, Maulita; Patayang, Mika (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Currently, we often encounter household waste and workshop waste, such as wood shavings, peanut shells and coconut fiber waste. Many studies have raised the topic of composite processing of each of them, but the potential of composite boards from a mixture of the three is not yet known. This study on the processing techniques for the combination of the three materials is needed so that the potential of the material can be explored more. The board was studied for its processing techniques using an experimental approach and qualitative methods. The form of the experiment in the form of physical and mechanical tests was carried out on the composite board, to then conduct further studies on the development of composite board products into women's fashion products in the form of bags through the preliminary design, development and finishing product methods. The results of this study were obtained composite materials of wood powder, peanut shell powder and coconut fiber having a board density of 0.8 gr/cm3 and MOR 2.06 kg/cm2, which means that the density of the particle board has a very low flexural strength and is not suitable for construction boards, but can be used as a material for making women's clutches. With the Preliminary Design, Design Development, and Final Design methods for composite board materials, an elegant clutch design was produced by displaying the distinctiveness of Indonesian culture, Kalimantan motif tumpar embroidery.